2013
DOI: 10.6007/ijarbss/v3-i12/436
|View full text |Cite
|
Sign up to set email alerts
|

Examine the Relationship between Religiosity and Social Capital

Abstract: Religion and religious beliefs are very important in individual and social life. So, the religious beliefs create a moral and social discipline, and it creates solidarity and cohesiveness in society and religion plays often a central role in the lives of individuals and communities. The main objective of this study was to examine the relationship between religiosity and social capital. This study had a main and three sub hypotheses that results show all of them are significant. The research method was descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…For example, congregations, in which people meet and build networks, exemplify how religious activities help to form social capital (Cloete, 2014). Akbari (2013), Fukuyama (2001), and Ghasemi and Amiri (2000) have documented a positive relationship between religiosity and social capital. For instance, Fukuyama (2001) contends that religion generates circumstances necessary for effective social relationships to create social capital.…”
Section: Social Capital and Social Cohesionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, congregations, in which people meet and build networks, exemplify how religious activities help to form social capital (Cloete, 2014). Akbari (2013), Fukuyama (2001), and Ghasemi and Amiri (2000) have documented a positive relationship between religiosity and social capital. For instance, Fukuyama (2001) contends that religion generates circumstances necessary for effective social relationships to create social capital.…”
Section: Social Capital and Social Cohesionmentioning
confidence: 99%
“…Churches and faith-based organizations provide a "fertile ground" for developing social cohesion (Heuser, 2005). Religious environments also create unity and cohesiveness in society (Akbari, 2013) and develop social and moral disciplines. With its nature of unity to satisfy the needs of the members in religious groups, social cohesion can create an environment to better supply nonprofits.…”
Section: Social Capital and Social Cohesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often referring to the classic work of Durkheim (1912), scholars have observed that religious involvement has a positive impact on social capital in the Netherlands (Bekkers & Schuyt, 2008;De Hart, 2014), the United States (Putnam & Campbell, 2012;Smidt, 2003;Wuthnow, 2002), Iran (Akbari, 2013) as well as in various cross-national studies (e.g. ; Kaasa, 2013;Lam, 2006;Ruiter & de Graaf, 2006).…”
Section: Controls: Religious Involvement and Background Characteristicsmentioning
confidence: 99%
“…Color has a different meaning from one culture to another culture. It can convey many meanings toward various groups of culture (Akbari, 2014;Mhatre (More), 2010). Color can be used to grab customers' attention and communicate unique messages to the customers.…”
Section: Visual Packaging Designmentioning
confidence: 99%